PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT TERHADAP HASIL BELAJAR PKN SISWA SEKOLAH DASAR - D. Wahyudin; Jennyta Caturiasari; Asri Apri Tri Lianti Putri (STKIP Subang, 2023)
Learning outcomes for each student are varied and not all students have high learning outcomes. This can be caused by various factors including factors that exist in the student who is less active during the learning process based on the lack of variety of learning models applied during the learning process, so that students do not understand the learning material properly. This study uses a cooperative learning model of teams games tournament type with the aim of knowing the improvement of student learning outcomes after using a cooperative learning model of teams games tournament type in class V and to determine the effect of cooperative learning model of teams games tournament type on student learning outcomes. With the research method used is pre experimental one group pre-test post-test design. The sample in this study was class V students totaling 28 people. The sampling used simple random sampling technique. Data collection in this study used tests and non-tests, namely questions about students' Civics learning outcomes and documentation. The results of this study state that the use of the teams games tournament type cooperative learning model has a positive effect on the Civics learning outcomes of elementary school students with a coefficient of determination (R Square) of 0.438 or 43.8% with an average N-Gain value of 46.59%. As well as having a significant difference between